Malaria‐Associated Secondary Hematophagocytic Lymphohistocytosis—A Case Report and Comprehensive Literature Review (sHLH) - Indresh Yadav; Sulav Kumar Jha; Sweta Singh; Dipesh Kumar Mandal; Saurav Jha (Clinical Case Reports, 2026)
ABSTRACT Malaria‐associated secondary HLH, though rare, is often overlooked. Clinicians should maintain a high‐index of suspicion in travelers returning from malaria‐endemic regions who develop severe to rapidly worsening inflammatory illness, as early recognition is critical for survival.